Cellulose pretreatment process - BRADT CHRIS; BENSON ROBERT; LEHOUX RICHARD ROMEO; BENECH REGIS-OLIVIER (2012)
A process for the production of ethanol from biomass is disclosed. The process relates to the pretreatment of corncob biomass and includes the steps of exposing corncob to steam in a reaction vessel at an elevated temperature and reaction pressure for a preselected exposure time. Volatile compounds are continuously vented during pretreatment. The reaction pressure is released for explosive decomposition of the corncob biomass into fibrous solids and condensate. The exposure is preferably carried out at a temperature of 190-210° C. and a pressure of 190 psig to 275 psig and an exposure time of 3 to 10 minutes.